Model Kecenderungan Perilaku Pemimpin Birokrasi - Fitriani Fitriani; Hesty Tambajong (Universitas Musamus, Merauke, Papua, 2022)
This study aims to create a model of behavioral tendencies of bureaucratic leaders in Papua Province. This research is a qualitative research with qualitative descriptive method and SWOT. Informants consist of academics, community leaders, and officials in the Papua Province environment. The behavior of bureaucratic leaders is very unique for each individual, and for the sake of good public service, good leader behavior is also needed. Bureaucratic leaders need competence in knowledge, experience and a mature attitude towards subordinates, superiors and partners as well as the community they serve. The results of this study found a behavioral tendency model for bureaucratic leaders in Papua Province to have a leadership type of limited free control and limited democracy, with a leadership style that is patterned towards results and cooperation. From the SWOT analysis, the suggestions given to improve the behavior of bureaucratic leaders are strategies for understanding the concept and implementation of leadership as well as fully understanding Papua's special autonomy, as well as setting oneself as an example, honing competence and providing space for subordinates to innovate;, for universities to be able to synergize in providing sustainable education in leadership programs and current government policies; for community leaders to be able to provide good input to the government and bureaucratic leaders; and the Papuan Provincial Government is expected to provide continuous socialization and training.